The Influence Of Product And Service Quality, And Promotion On Customer Loyalty Through Brand Image Marvee Clinic In Jakarta - Wida Feriningsih; Shirly Kumala; Indah Masri (Jurnal Info Sains : Informatika dan Sains, 2023)
The beauty business has become a huge industry that effects the daily life of many people. Every company competens to provide quality products, satisfactory service, maintain the expected brand imagein order to retain its customers. This study aims to determine the effect of product quality, service quality and promotion on customer loyalty through brand image. The research sample was 269 respondents who were clients who had done treatment at least 2 times with consultation (with best-selling products/drugs) or only buying best-selling products without consulting. Sampling was done by purposive sampling technique. The data analysis technique uses Structural Equation Modeling (SEM) analysis which is processed using software SmartPLS 3.4.3. The results of the study prove that product quality, service quality and promotion have an effect on brand image. Likewise, product quality and service quality have an effect on customer loyalty, but promotions have no effect on customer loyalty. Brand imageitself influences customer loyalty. Then brand imagesucceeds in mediating the effect of product quality on customer loyalty and the effect of service quality on customer loyalty and can also mediate the effect of promotion on customer loyalty.